Unjuk Kerja Down-Flow Hanging Sponge (DHS) Bioreaktor sebagai Secondary Treatment untuk Pengolahan Limbah Domestik - Faisal, Faisal; Machdar, Izarul; Muhammad, Syaifullah; Onodera, Takashi; Syutsubo, Kazuaki; Ohashi, Akiyoshi (Institution for Industrial Research and Standardization of Industry - Padang, 2017)
Wastewater pollution will continue to grow as the population and community activities continue to increase. Various techniques have been applied for domestic waste treatment, but generally these processes require relatively high operation and maintenance costs. Down Flow Hanging Sponge (DHS) has been proposed as a solution to the problem of handling domestic waste for developing countries. DHS bioreactor is a biological waste treatment that does not require an aerator and is easy to operate. This study aims to evaluate DHS bioreactors that can be applied in Indonesia. DHS bioreactor is operated with 4 hours hydraulic retention time (HRT). The results showed that DHS bioreactor is able to reduce up to 34% Chemical Oxygen Demand (COD) total, 33% soluble Chemical Oxygen Demand (COD), 80% Biological Oxygen Demand (BOD) total, and 65% Ammonia.ABSTRAK Pencemaran air limbah akan terus bertambah dengan meningkatnya jumlah penduduk dan aktifitas masyarakat. Berbagai proses telah diaplikasikan untuk pengolahan limbah domestik, tetapi umumnya proses-proses tersebut membutuhkan biaya operasi dan perawatan yang relatif mahal. Downflow Hanging Sponge (DHS) telah diusulkan sebagai pemecahan persoalan penanganan limbah domestik untuk negara-negara berkembang. DHS bioreaktor adalah pengolahan limbah secara biologis yang tidak membutuhkan aerator dan mudah dalam pengoperasian. Penelitian ini bertujuan untuk mengevaluasi bioreaktor DHS sehingga dapat diterapkan di Indonesia. Bioreakor DHS dioperasikan dengan hydraulic retention time (HRT) 4 jam. Hasil penelitian menunjukkan DHS bioreaktor mampu mengurangi hingga 34% Chemical Oxygen Demand (COD) total, 33% soluble Chemical Oxygen Demand (COD), 80% Biological Oxygen Demand (BOD) total, dan 65% ammonia.